Enhancing Learning Achievement through Effective Use of Teaching Aids in Islamic Education - Aisyah Jasadijaya; Rahmad Bala; Hasanah Purnamasari (International Journal of Learning Reformation in Elementary Education, 2023)
This study examined the impact of teaching aids on learning achievement in Islamic education. A questionnaire was used to collect data from fourth-grade students in Kupang, Indonesia. The questionnaire consisted of 20 items, and students rated their agreement on a 5-point Likert scale. Descriptive analysis showed that students' responses to teaching aids were categorized as moderate, with 42.1% falling into this category. The findings revealed a significant positive correlation between teaching aids and learning achievement. The coefficient of determination analysis indicated that teaching aids accounted for 88% of the variance in learning achievement. Furthermore, the t-test and simple linear regression analysis confirmed the significant influence of teaching aids on learning achievement. The study suggests that incorporating teaching aids and innovative learning strategies in Islamic education can enhance learning outcomes. Educators should use various teaching aids and media to create engaging learning environments. Policymakers should support effective teaching practices and provide necessary resources for integrating teaching aids in classrooms. These results offer valuable insights into the importance of teaching aids in improving learning achievement, not only in Islamic education but also in other subjects.